2005
DOI: 10.1111/j.1365-3059.2005.01184.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization ofGremmeniella abietinavar.abietinaisolates from Spain

Abstract: The taxonomic placement of Spanish isolates of Gremmeniella abietina var. abietina (Gaa) (race and biotype) was determined, for the first time, using RAPD markers and comparison of RAPD patterns for Spanish isolates and those originating from different regions of Europe and North America. Fifteen Spanish isolates of Gaa were isolated from recently dead shoots of 10 Pinus halepensis trees. Additionally, 17 isolates of Gaa from Canada, Finland, Switzerland and the USA, previously characterized according to race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Thus, based only on these analyses the Spanish population resembles another previously unknown biotype or species in Europe. This finding is in agreement with a previous study by Santamaría et al (2005), who showed that Spanish isolates are different from North American, B-and Alpine-type isolates. The results suggested low variability within Spanish population and a closer association to the EU race in North America.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Thus, based only on these analyses the Spanish population resembles another previously unknown biotype or species in Europe. This finding is in agreement with a previous study by Santamaría et al (2005), who showed that Spanish isolates are different from North American, B-and Alpine-type isolates. The results suggested low variability within Spanish population and a closer association to the EU race in North America.…”
Section: Discussionsupporting
confidence: 95%
“…Over the years, races, varieties, biotypes and species within Gremmeniella have been recognized through applications of different techniques, including conidial morphology (Petrini et al 1989), serology (Dorworth 1974), soluble protein electrophoresis (Petrini et al 1990;Lecours et al 1994), FAST profiles (Mü ller & Uotila 1997) and DNA fingerprinting techniques, such as RAPD (Santamaría et al 2005), ITS (Hamelin et al 2000), STS (Dusabenyagasani et al 2002) and RAMS (Hantula & Mü ller 1997;Kraj & Kowalski 2008). In this work, sequence analysis of the hypervariable SCAR marker GAAA1000 together with two other SCAR markers GAAA800 and ACA900 (Uotila et al 2006) was used to determine the degree of genetic differentiation of Spanish isolates with regard to the rest of European biotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It rarely produces apothecia in forests [22,41]. No local genetic differentiation was observed in biotype A [15] until the Spanish population was characterised [4,31]. In Spain, G. abietina has been found in northwestern P. halepensis plantations, and it seems to be a monoclonal population as a consequence of a founder effect [4].…”
Section: Introductionmentioning
confidence: 91%
“…The symptoms observed generally consist of dry needles, branches with some distortion of terminal twigs and eventual dieback or death of the trees (Santamaria et al, 2003). Spanish G. abietina is currently recognized as part of the European race (Santamaria et al, 2005) and has recently been related to biotype A, although it has a unique genotype (Botella et al, 2010).…”
Section: Introductionmentioning
confidence: 99%